Influence of land use intensity on ecological corridors and wildlife crossings’ effectiveness: comparison of 2 pilot areas in Austria - Mořic Jurečka; Richard Andrášik; Petr Čermák; Florian Danzinger; Christoph Plutzar; Roland Grillmayer; Tomáš Mikita; Tomáš Bartonička (Nature Conservation)
Human development and induced activities significantly affect the natural functioning of ecosystems and hence landscape connectivity. Ecological corridors are essential for maintaining structural as well as functional connectivity in cultural landscapes for wildlife, while providing interchange between core areas. In two pilot areas in the north-western and eastern part of Austria, ecological corridors were delineated using a geographic information system (GIS). The pilot areas are key to preserving ecological connectivity and are located along important international migration corridors (Bohemian Forest-Northern Alps corridor, Alpine-Carpathian corridor). Both areas are situated in highly human-altered and therefore dissected as well as fragmented landscapes. A one-year monitoring campaign using camera traps was carried out at selected locations along proposed ecological corridors in the cultural landscape and at wildlife crossings structures (WCSs) at intersections with road infrastructure. The monitoring was focused on mammals with a total of 18 species being observed. The most abundant species were roe deer, European hare and wild boar. European otter, European beaver, golden jackal and wildcat have only rarely been observed. Mammal species richness was positively correlated with the presence of vegetation cover and the coefficient of ecological stability (CES). The insights obtained can be used for recommendations and support in planning the planting of vegetation (use of grasslands, scattered and continuous woody vegetation, agroforestry systems) on the sites and in the vicinity of ecological corridors. The green bridges (wildlife overpasses) were used more frequently as well as by a larger number of mammal species compared to other studied WCSs showing characteristics that are less favourable for animals. The effectiveness of WCSs is mainly influenced by human activities, resulting in the recommendation to limit them on WCSs located along the routes of ecological corridors. We point out that actual wildlife migration corridors are likely to differ from designated data-driven ecological corridors generated by spatially explicit models, because these generally do not take into account all factors relating to the effectiveness of corridors. Our results suggest, that the application of the concept of functional connectivity is able to enhance the quality of ecological corridor designations, since usually they are based only on the concept of structural connectivity. For this reason, further studies are needed to help understanding factors and their specificities influencing the interplay between structural and functional connectivity of ecological corridors.